Body composition changes during and after curative chemotherapy in patients with testicular cancer - Semerad, Otakar; Buchler, Tomas; Vejmelka, Jiri; Rozsypalova, Aneta; Tomesova, Jitka; Kohout, Pavel (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2022)
BACKGROUND: Testicular cancer is associated with excellent prognosis and cure is achieved in most patients with advanced cancer treated with cisplatin-based chemotherapy. However, testicular cancer survivors are at increased risk of accelerated atherosclerosis, which significantly contributes to their late morbidity and mortality. Atherosclerosis is associated with a higher proportion of fat mass and especially with increased amount of visceral fat. We explored the effects of cisplatin-based chemotherapy on body composition during and after the treatment. PATIENTS AND METHODS: We studied 30 testicular cancer patients before chemotherapy, after the second cycle of chemotherapy and three months after the end of chemotherapy. Body composition parameters were evaluated using bioelectrical impedance analysis (BIA). RESULTS: Three months after the end of chemotherapy the fat mass had increased from 22.04±7.15% to 23.92±7.33% (P=0.026) and visceral fat volume had increased by 17% from 2.36±1.75l to 2.77±1.94l (P=0.013). In the whole sample there was a decrease in muscle mass after the second cycle of chemotherapy (-1.33 ± 2 kg on average; P=0.005). The changes in body composition varied according to distinct baseline fat mass. CONCLUSION: Cisplatin-based chemotherapy was associated with increase of fat mass, visceral fat, and body mass index. We also observed decrease in muscle mass and total body water. Our results suggest that BIA could help to target preventative measures to avert the acceleration of atherosclerosis in patients treated with cisplatin-based chemotherapy.
Keywords: cisplatina; body composition; Cisplatin; testikulární nádory; lidé; bioelectrical impedance analysis; Testicular Neoplasms; Male; elektrická impedance; složení těla; testicular cancer; index tělesné hmotnosti; Body Composition; chemotherapy; fat mass; mužské pohlaví; Body Mass Index; Electric Impedance; Humans